Spermadictyon suaveolens: A potential natural antimicrobial and antioxidant source - M Ajaib,; Uzma hanif,; Shazia Khalid, (International Journal of Phytomedicine, 2014)
The present work is an effort to discover ethnopharmacological effects, such as anti-microbial, MIC, antioxidant assay, viz; total antioxidant, total phenolic contents, ferric reducing antioxidant power (FRAP) and DPPH analysis. The crude extracts of bark and leaves of plant Spermadictyon suaveolens Roxb. was obtained in polar and nonpolar solvents viz; petroleum ether, chloroform, methanol and distilled water. The physical and chemical properties of plant extracts were determined like colour, texture, chemical nature and percentage yield. S. suaveolens bark extract in water exposed maximum yield, i.e. 2.3% The pathogenic bacterial and fungal strains used were including two gram positive bacteria (Staphylococcus aureus and Bacillus subtilis), three gram negative bacteria (Escherichia coli, Pseudomonas aeruginosa and Klebsiella pneumoniae) and three fungal strains(Aspergillus niger, Aspergillus oryzae and Fusarium solani). Maximum zone of inhibition of S. suaveolens was leaf methanolic extract against S. aureus, i.e. 32±9.60mm whereas petroleum ether extract of leaf displayed maximum zone against F. solani, 29±0.72mm. Methanolic extract of leaf of Spermadictyon suaveolens showed minimum inhibitory concentration (MIC) against gram positive S. aureus 0.03±0.0.01 at 0.9g/mL. Maximum percentage scavenging by DPPH assay was shown by the bark methanolic extract of S. suaveolens showed 78.317% at 500µg/mL.IC50 values methanolic extract of bark of S. suaveolens25.81µg/mL. Highest antioxidant activity was displayed by methanol extract of bark of S. suaveolens, i.e0.896±0.13. Leaf chloroform extract of S. suaveolens showed maximum FRAP value, i.e. 211µg/mL.